Perceived knowledge and perceptions toward biostatistics among dental and medical undergraduate students in International Islamic University Malaysia - Mohd Ibrahim, Mohamad Shafiq; Mohamad Zin, Ain Nadzirah; Haslim, Hani Zawani; Che Musa, Muhd Firdaus; Sayed Kamar, Syarifah Haizan (IIUM Journal of Orofacial and Health Sciences, 2022)
Research into dental and medical student on biostatistics may inform the educational policy changes. Therefore, it was vital to assess the level of knowledge and perception about biostatistics among dental and medical undergraduate students in order to determine their proficiency in this subject. A cross-sectional study was undertaken among dental and medical undergraduate students in International Islamic University Malaysia, Kuantan. The assessment of perceived and perception toward biostatistics was based on a 5-points Likert scale including 50 questions distributed into five domains to assess the knowledge, course value, difficulty, behavioural and expectations. A total of 158 out of 190 students responded to the questionnaire yielding a response rate of 83.2%. It was observed that more than 70% of students acknowledged that knowledge gained from biostatistics courses is useful to their future career, and almost 80% realized the relevance of biostatistics to real health issues. This study concludes that undergraduate dental students have almost similar and moderate level of knowledge in biostatistics as compared to the medical students. However, it is important to have additional practice and training through workshop to improve their level of comprehension in biostatistics.